Folic acid and iodine supplement use : a cross-sectional survey from preconception through to six weeks post-partum in New Zealand women : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Hunter, Brianna Rose (Massey University, 2023)
Background: Folic acid (FA) (0.8 mg and 5 mg for high-risk individuals) and iodine (150µg) supplements are recommended by the Ministry of Health (MOH) for pregnant and/or lactating women in New Zealand (NZ). Evidence suggests that many NZ women are not only taking FA and iodine in the form of a single nutrient supplement but are taking FA and iodine as part of a multivitamin (MVT) supplement which may or may not contain the recommended doses, and some are using a combination of both. No NZ study has examined the daily dose taken from both single nutrient supplements and MVT for both FA and iodine across all time periods. Aim: The aim of this study was to investigate what nutritional supplements containing FA and iodine were taken by postpartum NZ women, preconception, during the three trimesters of pregnancy and post-partum, and examine how well the women’s supplement use aligned with the NZ MOH recommendations. Methods: This cross-sectional observational study utilised data gathered on FA and iodine supplement use from an anonymous survey between February and August 2022. Descriptive statistics including frequency and percentages were reported. Folic acid and iodine weekly intakes from single nutrient supplements and MVT were calculated by multiplying the amount of nutrient in each supplement, with the number of times per day taken, and the average number of days taken per week reported. Binary logistic regression was used to identify the associations between the levels of FA and iodine supplement usage and selected sociodemographic characteristics. Results: A total of 584 women were included in the analysis. In addition to the single nutrient supplements for FA (0.8 mg and 5 mg) and iodine (150 µg), women took 28 different MVT. Fifty-eight percent (preconception; 30% from single nutrient supplements, 18% from MVT and 10% from both) and 96% (first trimester pregnancy; 61% from single nutrient supplements, 17% from MVT, and 19% from both) of women took FA-containing supplements. More than 75% of women reported taking iodine containing supplements during pregnancy (first and second trimesters: 93%, third trimester: 89%) and postpartum (76%). Approximately 60% took single nutrient supplements, 18% took only MVT and 14% took both. Based on the MOH recommendations, only 30% (preconception) and 62% (first trimester) achieved sufficiency of FA supplementation at 0.8 mg/day; 35% (preconception) and 69% (first trimester) achieved sufficiency of FA at 5 mg/day; around 50% women achieved sufficiency of iodine supplementation at 150 µg/day during pregnancy while only 37% during postpartum. The balance either took none, an insufficient dose or a dose that exceeded the recommended dose and many took them during non-recommended periods (FA after the first trimester; iodine preconception). Taking none or insufficient amounts of these nutrients was mostly associated with women who had been pregnant previously or had never used supplements before pregnancy. Conclusion: Most women reported taking FA and/or iodine-containing supplements at some point before, during and after their pregnancy. However, it is concerning that a large number of women do not seem to be taking them in accordance with the MOH recommendations in terms of both the dose and/or recommended time periods.
Keywords: 321001 Clinical nutrition